Water-soluble sulfonated hyperbranched poly(arylene oxindole) catalysts as functional biomimics of cellulases. Issue 13 (13th January 2016) - Yu, Feng; Smet, Mario; Dehaen, Wim; Sels, Bert F.
Abstract : A new polymer acid catalyst, sulfonated hyperbranched poly(arylene oxindole), 5-OH–SHPAO, was prepared for selective cellulose hydrolysis. Abstract : A new polymer acid catalyst, sulfonated hyperbranched poly(arylene oxindole), 5-OH–SHPAO, was prepared for selective cellulose hydrolysis. Its superior catalysis, showing high glucose selectivity at almost full cellulose conversion, is attributed to the presence of an hydroxyl group next to the sulfonic acid, therefore mimicking the separate acid–base pair in the cellulase active site.